The Adaptive Reuse of Kirkuk Citadel - Mokhtar, Mustafa; Korumaz, Mustafa (ICONARCH International Congress of Architecture and Planning, 2017)
Knowledge and memory influence the interpretations of a built environment, implying particular expectations in regard to the built environments and their roles in a society. People and their culture constitute the spirits of a building and a space. Memory also can dominate many heritage users, individuals, social and political groups over many centuries. Memory and spirit of cultural heritage enriches cultural identity under the global development. The adaptive reuse of heritage buildings is valued for the contribution for social and environmental sustainability as well as retaining memory. The inherent value of cultural heritage components and their place within the community’s memory helps to reinforce sense of place. In conservation sense identity, memory and the relationships of people give cultural significance to historical places. Evolution of the built environments bridges past and present to the future and embrace memory. However the cities as organisms are in a dilemma along with the loss of city memories and city spirits. These collective memories that bring spirits to a place play very important role and determine the cultural significance of places. The main contribution of this study is to emphasize the importance of adaptive reuse as a carrier of spirits to have a collective memory in order to sustain the development of a place. This article explores the relations between spirit and memory of a place by focusing of adaptive reuse project in Kirkuk citadel. Aim of this study is to question and evaluate restoration of Kirkuk Citadel in terms of urban identity and sense of place referring the early Kirkuk city and development of it. This paper also intends to put important guidelines for the future restoration projects of Kirkuk citadel – which is very urgently required – and high lights the importance of revitalizing this area, which is now the semi-dead heart of the city. The paper advocates policy makers is to increase the adaptive reuse policy as an integral tool of regeneration and sustainability policies in order not to lose collective memory.